In Vitro Evaluation of Bio Agents and Anti-bacterial Chemicals Against Ralstonia Solanacearum Causing Wilt in Brinjal (Journal of Plant Disease Sciences, 2019)
The studies were carried out on bacterial wilt caused by Ralstonia solanacearum on brinjal (Solanum melongena L.) during kharif 2014 at Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani. Bacterial wilt of solanaceous crops is a major limitation on the production of brinjal. An experiment on in vitro studies was carried out to find out the effectiveness of bioagents and anti bacterial chemicals to inhibiting the growth of R. solanacearum. All the different modes of bioagent treatment with different plant parts at 5, 10 and 20 per cent conc. and anti-bacterial chemicals at different levels of application evaluated in vitro (pot culture) on susceptible brinjal cv. Puneri Kateri were found antibacterial against R. solanacearum. However, bactericide combinations viz., copper oxychloride + streptocycline, Copper hydroxide + streptocycline and 2- Bromo, 2- Nitro Propane, 1, 3- Diol + streptocycline recorded significantly highest reduction in mortality 71.16, 64.88 and 55.95 per cent, respectively. Modes of treatment of bioagent P. fluorescens viz., Seed + root + soil and Root + soil recorded significantly highest reduction in mortality 67.16 and 60.71 per cent, respectively.
Keywords: Ralstonia solanacearu; Pseudomonas fluorescens; brinjal; wilt